Wine-related aromas for different seasons and occasions: Hedonic and emotional responses of wine consumers from Australia, UK and USA. (January 2019) - Ristic, R.; Danner, L.; Johnson, T.E.; Meiselman, H.L.; Hoek, A.C.; Jiranek, V.; Bastian, S.E.P.
Highlights: Berry-like were the most preferred aromas by 3000 consumers in an online survey. Similarly liked wine aromas were preferred in different contexts and seasons. Wine aroma emotion responses could explain context aroma preferences. Hedonic and emotional responses to wine aromas differed between demographicgroups. Abstract: It is still not fully clear how particular aromas in wine may affect consumers' liking and emotional responses, and whether these change in different contexts and seasons. Therefore, a study was conducted with 3000 regular wine consumers from Australia, UK and USA using an online survey that assessed liking for 59 wine aromas, and from which 9 aromas, selected as representatives of groups of similar aromas, were profiled for elicited emotions by the ScentMove™ scale. The most liked wine aromas across all countries were 'berry-like', followed by 'vanilla', 'chocolate', 'citrus-like' and 'honey'. Interestingly, aromas with the same liking rating displayed significantly different emotional profiles which seemed to drive differences in preferred consumption occasion and season. For example, highly liked 'passionfruit' aroma, associated with happy, relaxed and romantic emotions, was suitable for many occasions and seasons, 'lemon' evoked energetic emotions and was preferred in wines consumed at parties/BBQs in summer, while 'chocolate' would fit well in a restaurant. Hedonic and emotional responses towards selected wine aromas differed between various demographic groups. Gender, age and consumption frequency had greater effects than education or income, with similar patterns found in each country indicating similarity in wine cultures and the language used. The national influence was more reflected in the polarised rating by the USA consumers compared to UK and Australia. This information could be utilised to produce wines for specific occasions and seasons.